Evaluating femoral head collapse risk post-fixation removal: a finite element analysis - Li, Xishan; Zhou, Xiang; Yang, Jie; Böker, Kai Oliver; Schilling, Arndt F.; Lehmann, Wolfgang (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundFemoral neck fractures are prevalent in orthopedic injuries, often leading to complications such as nonunion and osteonecrosis of the femoral head (ONFH). Studies indicate that after healing and removal of internal fixation devices, some patients develop ONFH, while others experience osteosclerosis around the screw holes due to prolonged fixation, increasing ONFH risk. Despite such observations, biomechanical studies on this phenomenon are limited. This study assesses the risk of femoral head collapse post-internal fixation device removal and investigates the biomechanical effects of bone grafting at screw removal sites.MethodsUsing CT data, femoral anatomy was reconstructed. For control, the femoral head’s collapse area was identified. Experimental models, divided into those with and without bone grafts in screw holes, incorporated three fixation techniques, namely, triple cannulated screws (3CS), dynamic hip screws with cannulated screws (DHS+CS), and the femoral neck system (FNS), further subclassified into normal and sclerotic screw-hole models. Stress distribution, stress values, stress index, and strain range were assessed.ResultsIn both models, DHS+CS showed the highest stress in the overall model, while 3CS had the highest stress in the collapse area. The 3CS configuration also resulted in the largest strain range, which was observed in the central pillar of normal screw-hole models and the lateral pillar of sclerotic screw-hole models. The bone graft models exhibited lower peak, average stress, and strain values than the normal and sclerotic screw-hole models.ConclusionThe FNS screw hole demonstrates a relatively lower mechanical risk of femoral head collapse. In contrast, sclerotic screw holes increase this risk, while bone grafting may improve the biomechanical behavior after fixation removal, potentially reducing the likelihood of femoral head collapse.